Knowledge of Nurses regarding Nutritional management of Diabetes mellitus Patients in Tertiary Care Hospitals, Peshawar. - Saddar Badshah,; Samina Naz,; Shakir ullah,; Farhana Aziz,; Kinza Bibi,; Nazish Wahab,; Rafina Akhtar,; Tauheed Akhtar,; Nasir uddin, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Objective: To explore knowledge of nurses regarding nutritional management of diabetes mellitus patients in Tertiary Care Hospitals, Peshawar.Methods: A Cross sectional study was conducted among nurses. A self-made questionnaire of 20 questions regarding the basic knowledge about nutritional management of diabetes mellitus patients was distributed among 150 nurses selected by convenient sampling technique. Data were entered and analyzed by using SPSS version 22. In descriptive statistics frequencies and percentages were calculated for categorical variable and means and SD were calculated for continues variables. Chi-square was applied to determine any significant association between variables.Results: Results showed that that (54%) had poor knowledge about diabetic diet indicated by total knowledge of less than 60%, 21.3% of the nurses had average knowledge, while 13.33 % had good and only 13 % of the studied participants had excellent knowledge regarding diabetic dietary management which was above 80% score according to arbitrary scale on questionnaire. The study revealed that professional qualification, professional experience and gender of the participants has no significant association with knowledge level While significant value was found in LRH with knowledge level and professional qualification with a P value of 0.019.Conclusion: Based on the results of the current study, it is found that majority of the nurses have poor knowledge regarding diabetic diet especially nurses in LRH have comparatively lowest knowledge. It   directly affects the quality of care provided to the diabetic patients. It also raises concern about standard care.